ELABORACIÓN DE UN PLAN ESTRATÉGICO DE MARKETING PARA LA OPERADORA DE SERVICIOS TURÍSTICOS ECUAVANTUR DE LA CIUDAD DE LOJA - Cuenca López, Janeth Verenisse (2016)
He strategic marketing plan is considered a useful tool for the business sector, as it determines the steps, methodologies and time to achieve certain objectives. Allowing lead the way to reach a particular place. We can hardly produce it unless we know where we are and where we want to go. Then I therefore important to implement the present thesis project, which has as main objective the development of a strategic marketing plan for the operator ECUAVANTUR tourist services in the city of Loja; in order to cover the requirements of customers and know the weaknesses and strengths of the company to enable it to seize the opportunities presented to it and deal with the threats of the external environment and competition and will encourage managers in decision-making and strengthen it. The research was conducted based on information provided by key company officials (secretary general Manager / Accountant) by applying an interview and a survey of 373 potential clients (tourists) from the tour operator. As for the results obtained throughout the research process undertaken, are the following: in the external analysis with the application of the EFE matrix (assessment of external factors) it was determined that the weighted factor is 2.76 indicating that the organization is in an environment of opportunities. With regard to competitive profile matrix operator of tourist services ECUAVANTUR it is in a weak position compared to its competitors, 5 specifically advertising and market positioning, as the company that leads the industry is the operator Aratinga Aventuras. Through the EFI matrix (evaluation of internal factors), a weighted value of 2.54 was obtained, allowing us to determine the operator of tourist services remains strong domestic position, which ensures you can go ahead and develop so positive in between. Himself with the help of market research can demonstrate that 84% of respondents make use of the operator under study. With the above it is concluded that the strategic position of the outer Operator Travel Services ECUAVANTUR is fairly favorable; today presents opportunities especially in the rapid growth of tourism at national level, as well as the economic stability of the country, but there are still threats such as lack of security and variable inflation growth. Also internally the company has greater strengths than weaknesses among the main strengths that we have operator: performs market research, sales staff training, good customer service and its main weaknesses are the low participation in the market, limited advertising and promotion systems